Vitamin D and respiratory health in the Busselton Healthy Ageing Study. Issue 6 (24th January 2018) - Mulrennan, Siobhain; Knuiman, Matthew; Walsh, John P.; Hui, Jennie; Hunter, Michael; Divitini, Mark; Zhu, Kun; Cooke, Brian R.; Musk, Arthur W. (Bill); James, Alan
ABSTRACT: Background and objective: The relationship between vitamin D and respiratory disease was examined by cross‐sectional analysis of a large community‐based sample. Methods: Serum 25‐hydroxyvitamin D (25OHD) and history of respiratory disease, symptoms (recorded by questionnaire) and spirometry were measured in 5011 adults aged 45–69 years. Adjustments were made for age, sex, season and smoking (Model A), plus body mass index (BMI) and physical activity level (Model B), plus history of chronic diseases (Model C). Results: Mean (SD) age was 58 (SD 6) years with 45% males, 10% current smokers and 12% taking vitamin D supplements. The prevalence of 25OHD level <50 nmol/L was 8.0%. In all the three models, 25OHD <50 nmol/L was significantly associated with asthma (Model C: odds ratio (OR): 1.32; 95% CI: 1.00, 1.73), bronchitis (1.54; 1.17, 2.01), wheeze (1.37; 1.10, 1.71) and chest tightness (1.42; 1.10, 1.83). Participants with vitamin D level > 100 nmol/L had higher forced vital capacity (FVC) in all the three models (1.17% higher, compared with the 50–100 nmol/L group in Model C). Conclusion: Low levels of serum 25OHD were independently associated with asthma, bronchitis, wheeze and chest tightness after three levels of adjustment for potential confounders. Higher vitamin D levels were associated with higher levels of lung function. Abstract : Vitamin D in relation to respiratory disease was examined by cross‐sectional analysis of a large community‐based sample. Low levels of serum 25‐hydroxyvitamin D were independently associated with asthma, bronchitis, wheeze and chest tightness after three levels of adjustment for potential confounders. Higher vitamin D levels were associated with higher levels of lung function. Watch the video abstract See related Editorial